6.9x-3.6=24.0

Simple and best practice solution for 6.9x-3.6=24.0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6.9x-3.6=24.0 equation:


Simplifying
6.9x + -3.6 = 24.0

Reorder the terms:
-3.6 + 6.9x = 24.0

Solving
-3.6 + 6.9x = 24.0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3.6' to each side of the equation.
-3.6 + 3.6 + 6.9x = 24.0 + 3.6

Combine like terms: -3.6 + 3.6 = 0.0
0.0 + 6.9x = 24.0 + 3.6
6.9x = 24.0 + 3.6

Combine like terms: 24.0 + 3.6 = 27.6
6.9x = 27.6

Divide each side by '6.9'.
x = 4

Simplifying
x = 4

See similar equations:

| 6y^2=-7-2 | | 8/3x-21/2 | | 2x+15x^2=32 | | 5x5/5/7 | | 128=8-4e | | 45x+27= | | 2x+15x^2=35 | | x^3+5x^2-4x-2=0 | | 25=-5y-6x | | -6w^2+150w=0 | | 5(2x-17)=10x-85 | | 5x+x^2=y | | -13+3x+4+-5x=15 | | 0.06x-0.10(x-2)=0.02(8) | | 36+7-25+7= | | 4x-15/3=7 | | -2(7x-4)+3(5x-4)-3=7-3 | | 28+p=39 | | 10g+10=29g | | 17.40=1.5n | | 3y=8-2x | | 3x+4(x-8)= | | -7r+14=-71 | | -4(3x+6y)+12x+4y= | | 12x+.50y=112 | | 3cotx+3=8 | | 0=-15-3y+2x | | 25=x+2x+3x+1 | | z^2-6z+9+2i=0 | | (X-y)+2x+y=11+19 | | 10r^2-21=-4R+6 | | 3cot+3=8 |

Equations solver categories